Adolescents and Young Adults with Cancer: A Praxis Exploration on the Importance of Spirituality to Enhance Outcome and to Extend Life - York, Donald Oxford (Counseling et spiritualité, 2017)
Cancer is one of the leading causes of death worldwide. There are over 100 types of cancer that can affect anyone regardless of their gender, race, age and/or social status. Adolescents and young adults (AYA) 18-39 years old account for approximately 2% of the Canadian population with cancer. The AYA population is a new and upcoming population facing the physical, mental and emotional effects of the disease of cancer. It appears that insufficient research and resources exist for this understudied population. Cancer is a tragedy at any age but for the AYA population it occurs at a period that should be the one of most active stages of development, family and social life. The purpose of this research paper is to review the literature on the provision of AYA with cancer, their unique psychosocial needs and to understand the connectivity to spirituality in developing a better outcome and enhancing life.